1979
DOI: 10.1136/adc.54.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Congenital complete heart block in the newborn associated with maternal systemic lupus erythematosus and other connective tissue disorders.

Abstract: SUMMARY Four babies with complete heart block associated with maternal systemic lupus erythematosus (SLE) are described, together with a 5th baby whose mother had serological abnormalities only. One baby had a rapidly fatal outcome, one has required digoxin for heart failure, and the remaining 3 are asymptomatic but remain in complete heart block. Additional manifestations were present in 2 of them. The spectrum of neonatal abnormalities that may occur in association with maternal SLE and related connective ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Other less common manifestations can occur, including a haemolytic anaemia and thrombocytopenia [5.7], The major morbidity of NLE is associated with CHB. which has a !0 30% mortality and a significant morbidity, e.'^pecially if diagnosed early in life [22][23][24]. It has been suggested that the antibody response to the La protein and the 52-kD Ro protein are important in the development of CHB [3,8-11.25-27].…”
Section: Discussionmentioning
confidence: 99%
“…Other less common manifestations can occur, including a haemolytic anaemia and thrombocytopenia [5.7], The major morbidity of NLE is associated with CHB. which has a !0 30% mortality and a significant morbidity, e.'^pecially if diagnosed early in life [22][23][24]. It has been suggested that the antibody response to the La protein and the 52-kD Ro protein are important in the development of CHB [3,8-11.25-27].…”
Section: Discussionmentioning
confidence: 99%
“…Both mothers and babies have high mortality in systemic lupus erythematosus (SLE) pregnancies (1). In our patient with positive lupus anticoagulant (LAC), the fetus had high risks of abortion or stillbirth.…”
mentioning
confidence: 81%
“…Congenital complete heart block (CHB) results most commonly from an autoimmune process resulting in destruction of atrioventricular nodal conduction as well as myocardial inflammation 41 42. In the presence of an adequate junctional or ventricular escape rate, patients may remain asymptomatic though bradycardiac at rest and exhibiting a blunted maximum exercise heart rate.…”
Section: Disease-specific Clinical Presentationmentioning
confidence: 99%